Combined application of BMP-2 and naturally occurring bioactive factor mixtures for the optimized therapy of segmental bone defects. (February 2023) - Vater, Corina; Hetz, Michael; Quade, Mandy; Lode, Anja; Gelinsky, Michael; Rammelt, Stefan; Zwingenberger, Stefan; Bretschneider, Henriette
Abstract: Critical bone defects are the result of traumatic, infection- or tumor-induced segmental bone loss and represent a therapeutic problem that has not been solved by current reconstructive or regenerative strategies yet. Scaffolds functionalized with naturally occurring bioactive factor mixtures show a promising chemotactic and angiogenic potential in vitro and therefore might stimulate bone regeneration in vivo . To assess this prospect, the study targets at heparin-modified mineralized collagen scaffolds functionalized with naturally occurring bioactive factor mixtures and/or rhBMP-2. These scaffolds were implanted into a 2-mm segmental femoral defect in mice and analyzed in respect to newly formed bone volume (BV) and bone mineral density (BMD) by micro-computed tomography scans after an observation period of 6 weeks. To rate the degree of defect healing, the number of vessels, and the activity of osteoclasts and osteoblasts were analyzed histologically. The sole application of bioactive factor mixtures is inferior to the use of the recombinant growth factor rhBMP-2 regarding BV and degree of defect healing. A higher rhBMP-2 concentration or the combination with bioactive factor mixtures does not lead to a further enhancement in defect healing. Possibly, a synergistic effect can be achieved by further concentration or a prolonged release of bioactive factor mixtures. Statement of significance: The successful therapy of extended bone defects is still a major challenge in clinical routine. In this study we investigated the bone regenerative potential of naturally occuring bioactive factor mixtures derived from platelet concentrates, adipose tissue and cell secretomes as a cheap and promising alternative to recombinant growth factors in a murine segmental bone defect model. The mixtures alone were not able to induce complete bridging of the bone defect, but in combination with bone morphogenetic protein 2 bone healing seemed to be more physiological. The results show that naturally occuring bioactive factor mixtures are a promising add-on in a clinical setting. Graphical abstract: Image, graphical abstract